1996
DOI: 10.1128/aac.40.11.2517
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical aspects of antibiotic diffusion into microbial biofilms

Abstract: Antibiotic penetration into microbial biofilm was investigated theoretically by the solution of mathematical equations describing various combinations of the processes of diffusion, sorption, and reaction. Unsteady material balances on the antibiotic and on a reactive or sorptive biomass constituent, along with associated boundary and initial conditions, constitute the mathematical formulations. Five cases were examined: diffusion of a noninteracting solute; diffusion of a reversibly sorbing, nonreacting solut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
211
2
3

Year Published

1999
1999
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 404 publications
(220 citation statements)
references
References 30 publications
4
211
2
3
Order By: Relevance
“…We consider three simulations: The first is a numerical experiment that is similar to the analytic results in Stewart (1996) where the bulk fluid is well mixed and there is no external flow. The second incorporates explicit treatment of the external fluid with a fixed interface, and the final includes the motion of the biofilm and the external fluid.…”
Section: Simulation 2: Time Scale Of Disinfectionmentioning
confidence: 98%
See 2 more Smart Citations
“…We consider three simulations: The first is a numerical experiment that is similar to the analytic results in Stewart (1996) where the bulk fluid is well mixed and there is no external flow. The second incorporates explicit treatment of the external fluid with a fixed interface, and the final includes the motion of the biofilm and the external fluid.…”
Section: Simulation 2: Time Scale Of Disinfectionmentioning
confidence: 98%
“…The region is separated into two sub-regions, Ω (1) , the bulk fluid region, and Ω (2) , the biofilm region, by an interface Γ . reduced within the biofilm (Stewart, 1996). The reduction factor is not common for all chemicals, but is thought to be due to reduced permeability through physical and chemical interactions with the EPS.…”
Section: Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Physiological factors such as biofilm age [158], nutrient deficiency [162], and growth rate [163], have been suggested to affect the susceptibility to disinfectants. A second, more recent model proposes that physical properties of the biofilm limit the rate of transport and activity of sanitizers [113,[164][165][166][167][168]. Investigators suggested that transport of active agents from the delivery phase (typically the solvent) through the biofilm to the adhering interface (the surface of the medical or processing equipment) might be reduced due to physicochemical interactions of disinfectants with organic material or microorganisms in the upper layer of the biofilm matrix.…”
Section: Interaction Of Sanitizers With Biofilmsmentioning
confidence: 97%
“…Biocide Resistance. Biofilms protect microorganisms from activity of biocides because mass transfer is diffusion limited within the biofilm [149][150][151][152][153][154][155][156][157][158]. In order to effectively eradicate biofilms on surfaces, higher concentrations of biocides are often used (Fig.…”
Section: C35 Corrosion and Deteriorationmentioning
confidence: 99%